Corrigendum: An Integrated Management Model of Patients With Atrial Fibrillation: The Experience of the Local Health Unit Tuscany North-West/1 - listed], [No authors (Farmeconomia. Health Economics and Therapeutic Pathways, 2020)
There was an error in the description of GLORIA-AF registry program at page 10 in this Supplement by Casolo et al. [Farmeconomia. Health economics and therapeutic pathways 2019; 20(Suppl 1): 3-16; https://doi.org/10.7175/fe.v20i1S.1454]. The online version has been corrected on February 12, 2020.